Students Mathematical Critical Thinking Skills: Validity and Reliability with Winsteps and SPSS - Vebiyanti, Dewi; Salsabila, Khalisha; Bilhaki, Raden Roafli; Faradhilla, Ayu; Alyani, Fitri (Pattimura University, 2024)
It is of great importance to conduct validity and reliability testing in a study in order to ascertain the feasibility and effectiveness of the instruments employed. In this study, an analysis is required to ascertain the results of the validity and reliability tests on mathematical critical thinking skills utilising the SPSS and Winsteps applications. The research method employed was quantitative survey research, with a total of 133 high school students in the Jakarta and Depok areas comprising the sample population. The instrument designed to assess critical thinking skills comprises four indicators. The validity test on the mathematical critical thinking ability instrument with the SPSS application indicates that one value (value 11) is invalid, as evidenced by the Pearson correlation value. However, the remaining values meet the requirements for validity. The reliability value obtained through SPSS yielded a result of α = 0.75. The same results are observed when the Winsteps application is employed. One value (value 11) is identified as invalid, while the remaining values meet the criteria for the MNSQ outfit value, ZSTD outfit, and PTMEA-CORR. In addition, the reliability results obtained using Winsteps yielded a Cronbach's Alpha coefficient value of 0.87, indicating a high degree of reliability.